Global research on cysticercosis and neurocysticercosis: A bibliometric analysis - Gonzalez-Alcaide, Gregorio; Sosa, Nestor; Shevy, Laura; Belinchon-Romero, Isabel; Ramos-Rincon, Jose-Manuel (Frontiers in Veterinary Science, 2023)
Background Cysticercosis is a parasitic infection caused by Taenia solium. As a neglected tropical disease that is also difficult to diagnose, cysticercosis constitutes an important public health and research challenge. To characterize the development of research on cysticercosis and neurocysticercosis, considering the level of scientific evidence provided and the contribution of different countries to research, according to their endemic nature and their income level. Methods Indexed publications on cysticercosis and neurocysticercosis were retrieved from the MEDLINE database, and the evolution of scientific production and the topic areas addressed in the body of research were analyzed. Results A total of 7860 papers published between 1928 and 2021 were analyzed. The volume of annual publications increased over time, standing at over 200 documents/year since 2010. Case studies constitute the main study design (27.4% of the documents with available information, n=2155), with fewer studies that provide the highest levels of scientific evidence, such as clinical studies (1.9%, n=149) or systematic reviews (0.8%, n=63). The most productive journals belong to the Parasitology and Tropical Medicine categories. Although the USA is the most productive country (n=2292), countries where T. solium is endemic, such as India (n=1749), Brazil (n=941) and Peru (n=898) also stand out, as does Mexico (n=1414). However, other endemic countries in Latin America and sub-Saharan Africa show little participation in the research. The level of international collaboration by country is very uneven, with some countries presenting very low values, such as India (9.9% of documents in international collaboration) or Brazil (18.7%); while there is evidence of intense international collaboration in countries like Peru (91.3%), Tanzania (88.2%) or Kenya (93.1%). Research output has coalesced in three thematic clusters: basic research in animals; parasitism, animal health, and zoonoses; and the diagnosis and therapeutic approach in diseases associated with cysticercosis and neurocysticercosis. Conclusions The generation of knowledge on cysticercosis presents different features from other areas of research, such as the outstanding contribution of only some endemic countries; and the relevance of comprehensive approaches to research (animal and human health). Studies that provide higher levels of scientific evidence should be promoted, as should research in endemic areas.